SEKOLAH SEHAT TANPA KEKERASAN DAN ROKOK ANALISIS PROGRAM PENCEGAHAN DI KALANGAN PELAJAR - Saiful Bahri; Zamalludin Sembiring; Mutia Shifana; Hairun Nisak; Dahlia Harahap; Al Amin Lubis; Nova Maharani Lubis (LPPI UMN AL WASHLIYAH, 2025)
The healthy school program without violence and smoking is a systematic effort to create a safe, comfortable, and risk-free learning environment for students. This study aims to analyze the implementation of violence and smoking prevention programs in schools through community education and the development of positive school culture. The method used is a qualitative descriptive approach involving students, teachers, and school stakeholders as the subjects. Data collection instruments included field observations, semi-structured interviews, and simple questionnaires. The results showed that the implementation of prevention programs had an impact on increasing students’ awareness of the dangers of smoking and violence, fostering healthy peer communication, and building social support from teachers and the school environment. The conclusion of this study is that a healthy school program can be effective when combined with continuous education, creative campaigns, and consistent school regulations.